Risk of Non-melanoma Skin Cancer in Patients with Atopic Dermatitis Treated with Oral Immunosuppressive Drugs - Floor M. Garritsen; Jorien van der Schaft; Juul M. Reek; Klaziena Politiek; Harmieke van den Os-Medendorp; Marijke van Dijk; Dirk J. Hijnen; Marlies de Graaf; Carla A. Bruijnzeel-Koomen; Elke M. de Jong; Marie-Louise A. Schuttelaar; Marjolein S. Bruin-Weller (Medical Journals Sweden, 2017)
There is uncertainty about the risk of developing non-melanoma skin cancer (NMSC), including basal cell carcinoma and squamous cell carcinoma (SCC), in patients with atopic dermatitis (AD) treated with oral immunosuppressive drugs. A total of 557 patients with AD treated with these drugs in the University Medical Center Utrecht and Groningen, the Netherlands, were analysed. NMSC after oral immunosuppressive treatment was reported in 18 patients (3.2%). The standardized incidence ratio for developing SCC was 13.1 (95% confidence interval (95% CI) 6.5-19.7). Patients developing NMSC were older at the start of therapy (p<0.001) and data lock (p<0.001) compared with patients without NMSC. No significant differences were found in sex, cumulative days of oral immunosuppressive drugs and follow-up between these groups (p=0.42, p=0.88, and p=0.34, respectively). In interpreting these results it is important to include other factors, such as lack of association between treatment duration and tumour development and the long interval between treatment discontinuation and tumour development in some patients.